DIALOGUE AND PARTNERSHIP AMID RELIGIOUS PLURALISM - Chakkalakal, Pauline (Asian Horizons, 2020)
Indian Society is distinguished for its diversity of cultures, languages and religions. This pluralistic feature has been woven in the very fabric of our nation from time immemorial. We regard the diversity of religions and mutual interaction of religious traditions as a special blessing of our times that can contribute to the building up of an egalitarian society capable of overcoming the caste, creed, class, sex and gender based divisive forces.